Exploring the gut microbiota of Pacific white shrimp (Litopenaeus vannamei) suffering pale shrimp disease - Lalitphan Kitsanayanyong; Natnicha Chongprachavat; Tirawat Rairat; Arunothai Keetanon; Parattagorn Wimanhaemin; Niti Chuchird (PLoS ONE, 2025)
Pale shrimp disease is an emerging threat in Thailand, characterized by pale body coloration in Pacific white shrimp ( Litopenaeus vannamei ). Although the etiology had been identified as Photobacterium damselae subsp. damselae , the disease effects on gut microbiome remain poorly understood. This study investigated changes in the gut microbiota of Pacific white shrimp suffering from pale shrimp disease (diseased group) compared to disease-free shrimp (healthy group) collected from Surat Thani Province, Thailand. DNA extracted from the intestinal samples was subjected to 16S rRNA metagenomic sequencing, followed by taxonomic identification, diversity analyses, and functional prediction of the metabolic pathways. Despite a limited number of biological replicates, the occurrence of pale shrimp disease was able to reveal alterations in intestinal microbial composition, diversities, and functional features compared to the healthy shrimp. In most cases, the intestinal microbiota of the diseased shrimp were dominated by only 2 genera of bacteria, i.e., Photobacterium (54.63–70.53%) and Vibrio (24.94–26.12%), which together accounted for 79.58–95.47% of the total bacterial community. α-diversity, as indicated by the observed features, Shannon, and Simpson indices, was significantly decreased, and dominance was significantly increased in the diseased shrimp compared to healthy shrimp. Likewise, β-diversity was significantly different between groups; PCoA of un-weighted and weighted UniFrac clearly distinguished intestinal microbiota of the shrimp into 2 clusters, and ANOSIM of these data revealed statistical differences between groups, suggesting different microbiota communities between healthy and diseased shrimp. Moreover, diseased shrimp had significantly higher predicted functional features associated with bacterial virulence factors and antibacterial resistance. These exploratory findings suggest an association among pale shrimp disease, gut microbiota dysbiosis, and the proliferation of opportunistic taxa, particularly Photobacterium .